Pengaruh Konten Dakwah Digital pada Akun Instagram @husein_hadar terhadap Religiusitas Remaja - Bagus Ari Hermawan; Din Silmi Rahmawati; Tegar Isak Mahendra; Tria Aulia; Rena Yulia Wahyu Andita; Oktaviana Khoirun Nisa (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2024)
The expansion of social media has reshaped Islamic preaching practices and created new spaces for adolescents to encounter religious messages. This study investigates the influence of digital da'wah content on the Instagram account @husein_hadar on adolescent religiosity. A quantitative cross-sectional survey was conducted with 90 adolescents aged 12-21 years who actively used Instagram and had accessed or followed the account. Respondents were selected using purposive sampling, and data were collected through a Likert-scale questionnaire measuring exposure to digital da'wah content and religiosity. The data were analyzed using Pearson correlation, simple linear regression, and the coefficient of determination with SPSS. The results show a positive and statistically significant relationship between exposure to @husein_hadar's da'wah content and adolescent religiosity (r = 0.372, p < 0.001). Regression analysis further indicates that digital da'wah content significantly predicts adolescent religiosity (B = 0.432, β = 0.372, t = 3.759, p < 0.001). However, the coefficient of determination shows that the model explains 13.8% of the variance in religiosity, indicating a modest but meaningful contribution. These findings suggest that Instagram-based da'wah can function as a complementary medium for strengthening religious understanding and practice among adolescents, although religiosity remains shaped by broader family, educational, and social contexts. The study contributes empirical evidence to digital da'wah scholarship and highlights the need for more dialogical, contextual, and youth-oriented religious communication strategies.